The ion trap aerosol mass spectrometer: field intercomparison with the ToF-AMS and the capability of differentiating organic compound classes via MS-MS - J. R. W. Fachinger; S. J. Gallavardin; F. Helleis; F. Fachinger; F. Drewnick; S. Borrmann (Atmospheric Measurement Techniques, 2017)
Further development and optimisation of a previously described ion trap aerosol mass spectrometer (IT-AMS) are presented, which resulted in more reproducible and robust operation and allowed for the instrument's first field deployment. Results from this 11-day-long measurement indicate that the instrument is capable of providing quantitative information on organics, nitrate, and sulfate mass concentrations with reasonable detection limits (0.5–1.4 µg m−3 for 1 h averages) and that results obtained with the IT-AMS can directly be related to those from Aerodyne aerosol mass spectrometers. The capability of the IT-AMS to elucidate the structure of fragment ions is demonstrated via an MS4 study on tryptophan. Detection limits are demonstrated to be sufficiently low to allow for MS2 studies not only in laboratory but also in field measurements under favourable conditions or with the use of an aerosol concentrator. In laboratory studies the capability of the IT-AMS to differentiate [C4Hy]+ and [C3HyO]+ fragments at the nominal m∕z 55 and 57 via their characteristic fragmentation patterns in MS2 experiments is demonstrated. Furthermore, with the IT-AMS it is possible to distinguish between fragments of the same elemental composition ([C2H4O2]+ at m∕z 60 and [C3H5O2]+ at m∕z 73) originating from different compound classes (carboxylic acids and sugars) due to their different molecular structure. These findings constitute a proof of concept and could provide a new means of distinguishing between these two compound classes in ambient organic aerosol.